2018
DOI: 10.1007/s13555-018-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

Adapalene 0.3% Gel Shows Efficacy for the Treatment of Atrophic Acne Scars

Abstract: IntroductionScarring is an unfortunate clinical outcome of acne. Current treatment options for atrophic acne scars are dominated by non-pharmacological, invasive procedures which may not be suitable or affordable to all patients. This phase II, single-center, open-label, exploratory study assessed the efficacy, safety and subject-reported outcomes of adapalene 0.3% gel in the treatment of atrophic acne scars.MethodsThe study included subjects aged 18–50 years with past history of acne and moderate to severe fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…Screening of the reference lists of these papers resulted in one additional study, making the total 255. Of these 254 were excluded …”
Section: Resultsmentioning
confidence: 99%
“…Screening of the reference lists of these papers resulted in one additional study, making the total 255. Of these 254 were excluded …”
Section: Resultsmentioning
confidence: 99%
“…As both photodamaged skin and atrophic acne scars are associated with loss of dermal matrix, A0.3/BPO2.5 may exert a beneficial effect on pre-existing atrophic scars. A phase II pilot study in 20 subjects with a history of acne and moderate to severe acne scars receiving adapalene 0.3% for 24 weeks (once daily for 4 weeks then twice daily for 20 weeks) provided evidence for the improvement of atrophic scars with adapalene 0.3% [ 20 ]. Immunohistochemical analysis showed increased staining for procollagen-1 and collagen-3, supporting a remodeling effect of adapalene 0.3% gel, which was shown to improve skin texture and the appearance of atrophic acne scars, with a significant improvement in global scar grades [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the progressive incremental increase in efficacy and effect on scars observed with A0.3/BPO2.5 over 24 weeks highlights the importance of a longer duration of treatment. In fact, 3 months may be sufficient to observe resolution of the primary acne lesions, but the remodeling processes occur slowly, and 6 months may be required to induce significant stimulation of the dermal fibroblasts and collagen and clinically observe an effect on scars [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoids are frequently topically applied to improve several skin conditions. They are known to have an influence on dermal collagen synthesis [1], are utilized to reduce signs of skin aging [2][3][4] and have been shown to provide smooth atrophic acne scars [5,6]. Moreover, retinoids are known to activate fibroblasts, to increase type I procollagen and to decrease matrix metalloproteinase (MMP) expression in skin damaged by ultraviolet (UV) irradiation [1,7], to improve the skin texture and to reduce skin discoloration [8].…”
Section: Introductionmentioning
confidence: 99%